Second European Multi-Disciplinary Conference of National Strategies for Chlamydia Trachomatis and Human Papillomavirus (NSCP Conference) in Berlin, 2013 — Enhanced Detection, Management and Surveillance of Sexually Transmitted Infections in Europe are Essential!. (October 2013) - Ozolins, D.; D'Elios, M.M.; Ripa, T.; Bailey, R.; Timms, P.; Spiteri, G.; Haar, K.; Unemo, M.
There is a need for updated guidance on detection, management and surveillance of sexually transmitted infections (STIs). Chlamydia, gonorrhoea and syphilis reporting needs to be mandatory in more European countries to aid collection of data. More widespread Chlamydia screening is needed in many countries as this is the only way to reduce complications. The role of Human Papillomavirus (HPV) screening in a situation where the prevalence of HPV infection has dropped significantly was also discussed in the context of the high cost of screening, the need for a relatively complex infrastructure, particularly in developing countries, and falling vaccination costs. An integrated HPV vaccination and screening policy could be the most appropriate with vaccination at 9–13 years as recommended by WHO and a single HPV screen at 35–39 years, possibly repeated thereafter every 10 years. Female and male HPV vaccination programmes could lead to near elimination of genital warts in both females and males. Surveillance of STIs should be intensified where needed; additional or better quality data should be collected including reasons for testing, denominator data to estimate positivity rates, diagnostic methods, concurrent STIs, sexual orientation and country of acquisition; more analytical rather than descriptive epidemiology is needed.